Borehole thermometry data from Rutford Ice Stream, West Antarctica, 2007 - Smith, Andrew; Makinson, Keith; Nicholls, Keith (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
Borehole temperature measurements from the upper 300 m of Rutford Ice Stream. A string of thermistors was installed into a hot-water drilled hole in February 2005. The string comprised 10 calibrated thermistors at approximately 30 m spacing. The temperature measurements provided were taken in February 2007, following ample time for the heat from the drilling process to have dissipated. : In February 2005 a string of thermistors was lowered down the upper 300 m of a hot-water drilled borehole on Rutford Ice Stream (West Antarctica), once the drilling activities had been completed. Prior to deployment each thermistor had been calibrated. Wires to each thermistor extended down from the surface. The upper thermistor was positioned 15 m below the surface; below this, thermistors were spaced at 31.5 m intervals. Below ~60 m the hole was filled with water, above this it was air-filled. The top of the hole was then covered. Over time, the water in the borehole will have frozen and the excess heat remaining from the drilling activity will have dissipated. At various times over the following 2 years the temperature at the depth of each thermistor was determined by precise measurements of the resistance of each thermistor using the wires at the surface. The temperature measurements provided were taken in February 2007. : The thermistors used were 3K3A Betatherm. : Each thermistor was calibrated in a temperature-controlled water bath prior to deployment. Temperature-measurement accuracy was +/- 0.01 °C (Barret et al., 2009). The depth of each thermistor beneath the surface was accurate to better than +/- 10 cm at the time of installation.